2013
DOI: 10.1002/anie.201208293
|View full text |Cite
|
Sign up to set email alerts
|

Janus Micelles as Effective Supracolloidal Dispersants for Carbon Nanotubes

Abstract: Supracolloidal hybrids: Soft polymer‐based Janus micelles provide excellent stabilization for multi‐walled carbon nanotubes (see scheme) in a variety of solvents, including water. The size ratio of the micelle′s stabilizing corona to adsorbing corona (Janus balance) is decisive for good physisorption and stabilization. The supracolloidal interaction preserves the structural integrity of the nanotubes, which is essential for maintaining their useful properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 49 publications
1
57
0
2
Order By: Relevance
“…[261][262][263] Thus, applications that require interfacial stabilization may in the future benefit from the superior activity of Janus nanoparti-cles. Their potential use has been demonstrated recently in the compatibilization of homopolymer blends in lab-and industryscale extrusion equipment, 327,328 as colloidal dispersants for carbon nanotubes 329 and in emulsion polymerization. 330 Fig.…”
Section: Soft Janus Nanoparticlesmentioning
confidence: 99%
“…[261][262][263] Thus, applications that require interfacial stabilization may in the future benefit from the superior activity of Janus nanoparti-cles. Their potential use has been demonstrated recently in the compatibilization of homopolymer blends in lab-and industryscale extrusion equipment, 327,328 as colloidal dispersants for carbon nanotubes 329 and in emulsion polymerization. 330 Fig.…”
Section: Soft Janus Nanoparticlesmentioning
confidence: 99%
“…In particular, emerging strategies based on the self-assembly of block copolymers (BCPs) have enabled the construction of objects with multiple domains physically segregated on the nanoscale, making it possible to design multifunctional structures with a high degree of spatial control 8,9 . Such methods have enabled the synthesis of functional nanoscale materials of increasing complexity, including photonic crystals 10 , dispersants 11 , polymer vesicles 12,13 , monochromatic barcodes 14 and therapeutic nanoconstructs 15 .…”
mentioning
confidence: 99%
“…[14] Noncovalent modification of SWCNTs is particularly attractive because the strategy preserves the intrinsic properties of SWCNTs without disruption to the electronic and optical responses of the system. [15] It has been demonstrated that SWCNTs interact with conjugated species, such as pyrene derivates, [16] phthalocyanines, [17] porphyrins, [18] phenazine, [19] and thionine types of dyes, [20] based on π-π stacking. Twelve-membered cyclodextrins [21] and select DNA sequences [22] have also been reported to allow structure-specific recognition of SWCNTs with specific surface structure due to host-guest supramolecular complexation.…”
mentioning
confidence: 99%